2006
DOI: 10.1007/s00253-005-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved oxygen regime on growth dynamics of Pseudomonas spp during benzene degradation

Abstract: We investigated the effect of different oxygen regimes on growth patterns of Pseudomonas spp. during benzene degradation in microcosm batch studies. Benzene degradation was induced by limiting oxygen available for microbial activity, which consists of three initial-dissolved oxygen (DO) levels of oxic, hypoxic, and anoxic conditions. Batch experiments were performed for cell growth and benzene degradation by inoculating three strains of Pseudomonas spp. (Pseudomonas aeruginosa, Pseudomonas fluorescens, Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Recurrent evolution of a mat-forming ecotype occurred also in non-stirred microcosms of Pseudomonas evolution . We predict that in our system the non-mat ecotypes have diverged in other, yet unrecognized, ecological dimensions, perhaps by utilizing different chemical resources or by utilizing the more hypoxic, conic bottom of the tube (Mahendran et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent evolution of a mat-forming ecotype occurred also in non-stirred microcosms of Pseudomonas evolution . We predict that in our system the non-mat ecotypes have diverged in other, yet unrecognized, ecological dimensions, perhaps by utilizing different chemical resources or by utilizing the more hypoxic, conic bottom of the tube (Mahendran et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The growth patterns of the three Pseudomonas species during benzene degradation have been previously investigated under different oxygen regimes, namely, oxic, hypoxic, and anoxic regimes [39]. All of the strains used in the experiment were capable of growing under all oxygen regimes but in a different manner.…”
Section: Resultsmentioning
confidence: 99%
“…McKinley (2008) observed that alternating aerobic (4 mg/L dissolved oxygen for 8 hr) and anaerobic (0.8-1 mg/L dissolved oxygen for 16 hr) conditions stimulated concentrated biomass accumulation within the Organic carbon levels at the soil IS were 400-800% higher in soil exposed to aerobic/anaerobic conditions compared to sustained anaerobic conditions Krieg et al 1986 Oxygen stimulates EPS production Bayer et al 1990 EPS production by P. aeruginosa stimulated by oxygen Leitao and Sa-Correia 1993 Increased EPS production from P. aeruginosa under microaerophilic conditions Hassett 1996 EPS production by P. aeruginosa stimulated by oxygen Gamar-Nourani et al 1998 Microaerophilic conditions stimulated EPS over-production by bacteria Mathee et al 1999 EPS production by P. aeruginosa stimulated by oxygen Sabra et al 2002 Increased EPS production from P. aeruginosa under microaerophilic conditions Wyckoff et al 2002 Oxygen stimulates EPS production Akolkar and Lele 2004 Fermentative bacteria produced more EPS in a microaerophilic environment compared to anaerobic or aerobic conditions. Wilshusen et al 2004 Bacteria produced 250% more EPS under microaerophilic environment than anaerobic Mahendran et al 2006 EPS production by P. aeruginosa stimulated by oxygen media relative to strictly anaerobic conditions. This accumulation was confirmed visually and through measurements of pressure loss across the porous media.…”
Section: Oxygen and Accumulation Of Organic Mattermentioning
confidence: 99%